Constituent Elements, pH and Electrical Conductivity Values of Feedstock, Ash and Slow Pyrolysis Derived Biochar of Date Palm Wastes - Ghanbar Ebrahimi; Alireza Shaker; Peyman Ahmadi; Mosayeb Dalvand; Masoud Shafie (Drvna Industrija)
Date palm wastes (rachis and dried stems) are feasible biomass to be treated and used for soil improvement and restoration purposes. Identified properties of processed forms of such biomass are required for their deliberated applications in compensating for any types of soil deficiencies. For this task constituent elements, pH and electrical conductivity (EC) values of fiber bundles, ash and slow pyrolysis derived biochar of these wastes were determined. Test materials were from two palm groves, differentiated by governing ecological conditions, named tropical and dry zones, to study climate impacts on the same palm species. Experimental data have shown that discrepancies in the percentages of C, H, N and S in three types of waste from the humid zone are not drastic. Their ashes are alkaline, but feedstock and biochar are acidic. EC values are high in ashes, but low in feedstock and biochar. C/N ratios do not change considerably. The same results were also observed for dry zone wastes, except their C/N ratio which is drastically higher. Percentages of measured properties of wastes from sampled groves were also compared for climate impacts. In terms of properties, differences between three forms of waste from two groves require to be considered when used for soil improvement purposes.